Seven Years in Tibet - Harrer, Heinrich; Translated by Graves, Richard and Wuth an Introduction by Fleming, Peter (London Rupert Hart-Davis, 1953)
An account of an Austrian mountain climber's escape from a British internment camp in India during World War II and his twenty-one-month journey through the Himalayas to safety in the Forbidden City of Lhasa in Tibet.
Includes Illustrations
Keywords: Tibet Autonomous Region (China) -- Description and Travel -- Travel